Fuzzy Semi-Numbers and Their Elementary Arithmetic With a Medical Case Study - Sh. Yeganehmanesh; M. Amirfakhrian; P. Grzegorzewski (International Journal of Computational Intelligence Systems, 2018)
A new methodology for processing non-normal fuzzy sets is proposed. To break the predominant constraint on normality of fuzzy numbers the concept of fuzzy semi-numbers is introduced Then it is shown how to generalize operations defined on fuzzy numbers onto a family of fuzzy semi-numbers with possibly different heights.